Long-term Late Cretaceous oxygen- and carbon-isotope trends and planktonic foraminiferal turnover: A new record from the southern midlatitudes - Falzoni, F.; Petrizzo, M. R.; Clarke, L. J.; MacLeod, K. G.; Jenkyns, H. C. (Geological Society of America Bulletin, 2016)
The ∼35-m.y.-long Late Cretaceous greenhouse climate has been the subject of a number of studies, with emphasis on the Cenomanian–Turonian and late Campanian–Maastrichtian intervals. By contrast, far less information is available for the Turonian–early Campanian interval, even though it encompasses the transition out of the extreme warmth of the Cenomanian–Turonian greenhouse climate optimum and includes an ∼3-m.y.-long mid-Coniacian–mid-Santonian interval when planktonic foraminifera underwent a large-scale, but poorly understood, turnover. This study presents ∼1350 δ18O and δ13C values of well-preserved benthic and planktonic foraminifera and of the <63 μm size fraction from the Exmouth Plateau off Australia (eastern Indian Ocean). These data provide: (1) the most continuous, highly resolved, and stratigraphically well-constrained record of long-term trends in Late Cretaceous oxygen- and carbon-isotope ratios from the southern midlatitudes, and (2) new information on the paleoecological preferences of planktonic foraminiferal taxa. The results indicate persistent warmth from the early Turonian until the mid-Santonian, cooling from the mid-Santonian through the mid-Campanian, and short-term climatic variability during the late Campanian–Maastrichtian. Moreover, our results suggest the cause of Coniacian–Santonian turnover among planktonic foraminifera may have been the diversification of a temperature- and/or salinity-tolerant genus (Marginotruncana), and the cause of the Santonian–early Campanian extinction of Dicarinella and Marginotruncana may have been surface-ocean cooling and competition with globotruncanids.